‘RELIGION AND THE STATE’ BOOK REVIEW: THE CONTEXT OF RELIGIOUS-BASED CONSUMPTION IN INDONESIA - Syahdina, Rafika; Aulia, Guruh Ryan (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2025)
This review aimed to discuss the topic from the Paper by Dawood Ahmed and the Book from Jack Barbalet. Both writings discussed about the relation between religion and the state which then connected in seeing how people relate their spirituality with their bought goods. This writing explores the dynamic interplay between religion, consumer behavior, and state policy in the context of modern capitalist societies. As consumerism becomes increasingly embedded in cultural norms, the demand for religious attributes in products—such as halal labels or symbolic branding—reflects a convergence of spiritual identity and market participation. This writing also highlights how religious practices can stimulate economic growth, particularly when facilitated by a pluralist or neutral state framework. Using Indonesia as a primary case, where Pancasila enshrines belief in God without adopting a theocratic model, the paper illustrates how religious consumer demands have spurred regulatory and commercial responses.